The role of industrial factors on optimal capital structure proxy: an empirical study on Indonesia manufacture companies - Naomi, Prima; Ekaputra, Irwan Adi; Wibowo, Buddi (Serbian Journal of Management, 2018)
The objective of this study is to improve the model of optimal capital structure. This research aims to investigate the role of the industrial factors on the optimal capital structure proxy by including industry factors in the existing model and using the company characteristic variables as control variables. This research applies seven industrial variables: 1) Number of Firms in Industry (NFI), 2) Industry Competitive Dynamic (ICD), 3) Firm Response to Industry Competitive (FRI), 4) Numbers of Employees in an Industry (NEI), 5) Employees’ Share of Firm Quasi Rents (ESQ), 6) Category of Product Diversificatio (CPD), and 7) Diversification level of Relatedness (DRD). This research determines whether the proposed proxy in this research is better than the two other proxies. The testing procedure is designed to replicate the procedure of Farhat (2003). The data used in the study consist of 83 companies from 13 industries listed on IDX for the period of 2001-2014. The results showed that the industry variables can improve the existing optimal capital structure proxies. This finding contributes to the industry in that it can improve the dynamic trade-off model of capital structure.